An analysis of fertility differentials by religion in Kerala state: A test of the interaction hypothesis - MANOJ ALAGARAJAN (Population Research and Policy Review 22: 557-574, 2003., 2003)
In a re-evaluation of overall decline to below replacement fertility in the Kerala state of India, it was generally found that fertility among Muslims is higher and contraceptive prevalence lower than among Hindus and Christians. This paper examines the interaction between religion and other socioeconomic factors, that is, whether the effect of religion on fertility remains constant across other factors. The analysis is based on the data from the National Family Health Survey-1 in Kerala. The analysis found that large Hindu-Muslim fertility differences at a low level of education do not persist at higher levels. For contraceptive use, wider gaps are found at a middle level of education and at a medium level of standard of living than at lower and higher levels. This indicates that couples at different socioeconomic settings make different decisions in spite of belonging to the same religion. The fact that fertility of Muslims at higher levels of socioeconomic status is low, and not much different than the fertility of other religions, suggests that the observed fertility gap between Hindus/Christians and Muslims is a passing phenomenon.